Digital transformation and green innovation: firm-level evidence from China - Wang, Xiaoyan; Zhong, Xiangfei (Frontiers in Environmental Science, 2024)
The technological source of green innovation has been a persistent theme in environmental economics. In more recent years, digital technology has triggered a new round of social changes and been viewed as the emerging growth engine, leading to significant improvements in productivity and innovation. However, whether the digital technology can promote green innovation remains an unknown issue. This study elucidates the causal relationship between digital transformation and green enterprise innovation for Chinese companies during 2009-2019. The findings indicate that digital transformation positively affects the quantity and quality of green innovation performance.Each standard deviation increase in the degree of digital transformation increases the quantity and quality of green enterprise innovation by 2.924% and 2.124%, respectively. Additionally, digital transformation drives green innovation by alleviating financing constraints and information asymmetries and by improving human capital. This effect is more pronounced among enterprises in regions with high levels of environmental investment, clean industries, and stringent environmental regulations. By highlighting the linkage between firm-level digital transformation and green innovation, this study contributes to our understanding of the positive environmental externality associated with the diffusion of digital technology and offers valuable insights for the sustainable development of emerging economies.